Analisis Investasi Pembangunan Proyek Spam (Sistem Penyediaan Air Minum) Kota Bandar Lampung - Nabila, Andri Abyan; Kustiani, Ika; Siregar, Amril Ma'ruf (Universitas Lampung, 2021)
In an effort to meet the needs of drinking water for the community, the city government of Bandar Lampung pioneered the development of a Drinking Water Supply System (SPAM), the authors reviewed the analysis of investment in the construction of the Bandar Lampung City SPAM project. The purpose of this study was to determine the feasibility of a SPAM development project assessed from financial parameters. In this study, the feasibility of the economic aspect was carried out by reviewing the following assessment parameters, namely Net Present Value (NPV), Benefit Cost Ratio (BCR), Internal Rate of Return (IRR) and Payback Period (PP). The data used are detailed data on SPAM cost budget, SPAM working drawings and water consumption levels, as well as data from BI in the form of interest rates and inflation rates. From the analysis, it can be concluded that the inflation rate in Indonesia is based on a projection for 25 years, namely between 4% -10% per year, the BI rate based on projections in 2018-2057 ranges from 6% -12% per year, the total investment in SPAM development is Rp. .750,000,000,000.00, from the existing scenario it is concluded that the Bandar Lampung SPAM development project is not financially feasible. However, SPAM development is economically feasible because it increases water availability and the coverage of existing services and also expands regional development in the city of Bandar Lampung.Keywords: analiysis, SPAM, scenario